Smartphone operating system openness and application pricing. - Cheah, Hui Yang. (2010)
The smartphone operating system and application markets are fast growing and high valued. We investigate the strategies of smartphone operating systems and applications developers through two theoretical models. This paper first solves the sequential location-price problem of smartphone companies in a duopoly situation, given an asymmetric triangular consumer distribution and horizontal consumer preference on the OS openness level of the two smartphone companies. We apply the analysis to Apple and Google and conclude that Apple has first mover advantage and always captures larger market share. Both of the two firms tend to move towards more open positions in the future. In the second model we look at the pricing and market decision of application developer firms. This paper provides a clear pricing guideline for developer firms which require little market research. Besides, the necessary conditions for developer firms to sell to two markets and the rationale for free applications, discount, different pricing in two markets are also discussed in this paper.